L = 10 mw = 11 mh = 5 md = 15.6844 mS = 430 m²V = 550 m³ x 2 = 1100m³
Agenda:l = lengthw = widthh = heightd = diagonalS = surface area V = volume
925 ÷ 8
9 ÷ 8 = 1 r1
put 1 before the 2 = 12
12 ÷ 8 = 1 r 4
4 before 5 = 45
45 ÷ 8 = 5 r 5
So it's 115 r 5
115 and 5/8 refered
![\bf 7~~,~~\stackrel{7+6}{13}~~,~~\stackrel{13+6}{19}~~,~~\stackrel{19+6}{25}\qquad \impliedby \qquad \textit{common difference "d" is 6}](https://tex.z-dn.net/?f=%5Cbf%207~~%2C~~%5Cstackrel%7B7%2B6%7D%7B13%7D~~%2C~~%5Cstackrel%7B13%2B6%7D%7B19%7D~~%2C~~%5Cstackrel%7B19%2B6%7D%7B25%7D%5Cqquad%20%5Cimpliedby%20%5Cqquad%20%5Ctextit%7Bcommon%20difference%20%22d%22%20is%206%7D)
we know all it's doing is adding 6 over again to each term to get the next one, so then
![\bf \stackrel{\textit{Recursive Formula}}{\stackrel{\textit{nth term}}{f(n)}~~=~~\stackrel{\textit{the term before it}}{f(n-1)}~~~~\stackrel{\textit{plus 6}}{+~~~~6}}](https://tex.z-dn.net/?f=%5Cbf%20%5Cstackrel%7B%5Ctextit%7BRecursive%20Formula%7D%7D%7B%5Cstackrel%7B%5Ctextit%7Bnth%20term%7D%7D%7Bf%28n%29%7D~~%3D~~%5Cstackrel%7B%5Ctextit%7Bthe%20term%20before%20it%7D%7D%7Bf%28n-1%29%7D~~~~%5Cstackrel%7B%5Ctextit%7Bplus%206%7D%7D%7B%2B~~~~6%7D%7D)
now for the explicit one
![\bf n^{th}\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ d=\textit{common difference}\\[-0.5em] \hrulefill\\ a_1=7\\ d=6 \end{cases} \\\\\\ a_n=7+(n-1)6\implies a_n=7+6n-6\implies \stackrel{\textit{Explicit Formula}}{\stackrel{f(n)}{a_n}=6n+1} \\\\\\ therefore\qquad \qquad f(10)=6(10)+1\implies f(10)=61](https://tex.z-dn.net/?f=%5Cbf%20n%5E%7Bth%7D%5Ctextit%7B%20term%20of%20an%20arithmetic%20sequence%7D%20%5C%5C%5C%5C%20a_n%3Da_1%2B%28n-1%29d%5Cqquad%20%5Cbegin%7Bcases%7D%20n%3Dn%5E%7Bth%7D%5C%20term%5C%5C%20a_1%3D%5Ctextit%7Bfirst%20term%27s%20value%7D%5C%5C%20d%3D%5Ctextit%7Bcommon%20difference%7D%5C%5C%5B-0.5em%5D%20%5Chrulefill%5C%5C%20a_1%3D7%5C%5C%20d%3D6%20%5Cend%7Bcases%7D%20%5C%5C%5C%5C%5C%5C%20a_n%3D7%2B%28n-1%296%5Cimplies%20a_n%3D7%2B6n-6%5Cimplies%20%5Cstackrel%7B%5Ctextit%7BExplicit%20Formula%7D%7D%7B%5Cstackrel%7Bf%28n%29%7D%7Ba_n%7D%3D6n%2B1%7D%20%5C%5C%5C%5C%5C%5C%20therefore%5Cqquad%20%5Cqquad%20f%2810%29%3D6%2810%29%2B1%5Cimplies%20f%2810%29%3D61)
Two equations
let c the calories in carrot
let h the <span>calories in </span><span>hershey's kisses
</span><span>
4c + 8h = 230 eq 1</span>
10 c + 7 h = 263 eq 2
to solve the solution we multiply eq 1 by 10
we multiply <span>eq 2 by 4
</span>
40 c + 80 h = 2300
40c + 28 h = 1052
we subtract the two equations we get
52 h = 1248
h= 24
and so in replacing h = 24 in the equation we get c = 9.5
Answer: For the equation simply substitute 30 in for v and 4 in for s in the equation given, so H=-16t^2+30t+4
Part 2.
If the juggler misses the ball, you wish to know the time that it takes for the ball to travel the four feet from his hand to the ground, so respectively,
4=-16t^2+30t+4 or 0=-16t^2+30t or 0 = -16t+30,
solving for t, t =30/16 seconds or 1.875 seconds
Step-by-step explanation: